2006
DOI: 10.1264/jsme2.21.16
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in situ Detection of Two Lineages of Bacteroidales Ectosymbionts Associated with a Termite Gut Protist, Oxymonas sp.

Abstract: Bacterial attachments often cover the entire surface of flagellated protists in the guts of termites. Based on PCR-amplified 16S rRNA gene sequences, we investigated the phylogenetic positions of the rod-shaped bacteria (ectosymbionts) attached to the protist Oxymonas sp. in the termite Neotermes koshunensis. Two distinct and unique lineages of the ectosymbionts within the order Bacteroidales were identified, each belonging to a cluster exclusively comprised of the sequences from termite gut. We designed two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Interactions via the exchange of metabolites between the "Synergistes" ectosymbionts and the host Caduceia protist, as well as between the "Synergistes" and Bacteroidales ectosymbionts, remain to be clarified. Bacteroidales ectosymbionts have been commonly and abundantly found in association with diverse protist species from the guts of various termite species and a cockroach (17,26,27,34). Since Bacteroidales ectosymbionts, though members of a lineage distinct from that identified in the present study, have also been found on M. paradoxa cells that harbor spirochetal motility symbionts (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…Interactions via the exchange of metabolites between the "Synergistes" ectosymbionts and the host Caduceia protist, as well as between the "Synergistes" and Bacteroidales ectosymbionts, remain to be clarified. Bacteroidales ectosymbionts have been commonly and abundantly found in association with diverse protist species from the guts of various termite species and a cockroach (17,26,27,34). Since Bacteroidales ectosymbionts, though members of a lineage distinct from that identified in the present study, have also been found on M. paradoxa cells that harbor spirochetal motility symbionts (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…The cellular association of bacteria and protists is a prominent feature of gut microbiota in lower termites. [35][36][37] The endo-and ectosymbiotic bacteria of gut protists comprise diverse taxonomic groups: Treponema, [38][39][40][41] ''Endomicrobia,'' [42][43][44] Bacteroidales, 28,40,[45][46][47][48][49][50][51] Deltaproteobacteria, 52) Mycoplasmatales, 53) and Synergistetes. 28) Among these, Treponema and Bacteroidales are the most frequently observed ectosymbionts of gut protists.…”
Section: In Situ Localization Of Termite Gut Bacteriamentioning
confidence: 99%
“…One unique characteristic of the termite-gut community is its highly structured nature. Specific associations of various prokaryotes such as methanogenic archaea 3,20) , spirochetes 6,13,21) , Bacteroidales members [10][11][12]21) , and the candidate phylum Termite Group 1 of bacteria 17) , with the cells of gut protists are frequently observed.…”
mentioning
confidence: 99%